Measuring coordination between land ecological security and high-quality economic development: a case of the Beijing-Tianjin-Hebei region - Zhong, Xiaoyong; Guo, Dongyan; Tang, Yandong; Chuai, Yafei (Frontiers in Environmental Science, 2025)
The interplay between land ecological security (LES) and high-quality economic development (HED) is intricately linked to the sustainable development of regions, with their combined influence at the county level being pivotal for the harmonious growth of urban agglomerations. In this study, we employ the entropy-weighted technique for order preference by similarity to ideal solution (EW-TOPSIS), coupling coordination degree (CCD), deviation coordination degree, and relative development degree methodologies to assess the developmental status of LES and HED, as well as the coupling coordination between these two systems, and introduce a novel approach for delineating functional regions. Our findings reveal a pronounced polarization of LES and HED within the Beijing-Tianjin-Hebei (BTH) region, with the majority of areas exhibiting a high degree of coupling but moderate imbalance. Spatial analysis highlights distinct characteristics, allowing for the segmentation of the region into seven distinct development functional zones. Recommendations include the establishment of a collaborative framework for the BTH region, enhancing the innovation, openness, and coordination within HED, and focusing on the advancement of HED in leading, key, and stable development areas. Furthermore, it is essential to elevate the visibility and responsiveness of LES, and strategically implement land ecological engineering in key and stable development areas. These strategic initiatives aim to improve the developmental standards of LES and HED, thereby enhancing the coordination and synergy between these two key systems.